The Financial Ratio Analysis in Predicting the Conditions of Financial Distress - Meilinda Dwi Astuti; Sri Hermuningsih; Alfiatul Maulida (Almana : Jurnal Manajemen dan Bisnis, 2021)
Financial distress is a stage of decline in a company's financial condition that occurs before bankruptcy or liquidation. The Indicators of financial distress from results of the test scores using financial ratios, financial ratios are figures obtained from results comparisons between one financial statement item and another that have a relevant and significant relationship. The purpose of this study is to examine the effect of financial ratios to predict financial distress on manufacturing companies in Indonesia Stock Exchange. The research population was all manufacturing companies listed on the Indonesia stock exchange, period 2015-2019. The research sample used the purposive sampling technique. The data analysis method used logistic regression analysis. The results showed liquidity, leverage, and activity profitability, respectively simultaneously affect financial distress. Partially profitability has a positive effect on financial distress. Liquidity, leverage, and activity have negatively affected financial distress in manufacturing companies listed on IDX from 2015 to 2019.